Photocatalytic activity of functionalized nanodiamond-TiO2 composites towards water pollutants degradation under UV/Vis irradiation - Luisa M. Pastrana-Martínez (2018)
Pristine nanodiamonds (NDs) obtained by detonation, or functionalized by different treatments, namely oxidation, hydrogenation and amination, were used to synthesize composites by insertion in TiO2 matrixes. The different treatments of the NDs lead to materials containing diverse texture properties and surface chemistry functionalities, particularly concerning the insertion of nitrogen and oxygen groups. The photocatalytic activity of the prepared composites was evaluated for the oxidative degradation of two water soluble pharmaceuticals - diphenhydramine and amoxicillin - under near-UV/Vis irradiation. The most active photocatalyst in what concerns both pollutants degradation under near-UV/Vis irradiation was the composite containing pristine NDs (NDDT). The photocatalytic performances were dependent on the specific surface area and on the amount of functional groups incorporated over the NDs. The influence of ND in the composites activity is well correlated with the observed photoluminescence quenching of TiO2, which corresponds to a delay in the recombination rate of charge carriers that benefices the photocatalytic reaction. Scavenging of photogenerated holes and radicals by employing sacrificial hole and radical agents revealed that the holes played the main role on both pollutants degradation under UV/Vis irradiation. Reutilization experiments proved that the ND composites have good stability and reusability.